Common and unique mechanisms of Chinese herbal remedies on ischemic stroke mice revealed by transcriptome analyses. (15th September 2015) - Shen, Yuh-Chiang; Lu, Chung-Kuang; Liou, Kuo-Tong; Hou, Yu-Chang; Lin, Yun-Lan; Wang, Yea-Hwey; Sun, Hsing-Jen; Liao, Ko-Hsun; Wang, Hsei-Wei
Abstract: Ethnopharmacological relevance: Four traditional Chinese herbal remedies (CHR) including Buyang Huanwu decoction (BHD), Xuefu Zhuyu decoction (XZD), Tianma Gouteng decoction (TGD) and Shengyu decoction (SYD) are popular used in treating brain-related dysfunction clinically with different syndrome/pattern based on traditional Chinese medicine (TCM) principles, yet their neuroprotective mechanisms are still unclear. Materials and methods: Mice were subjected to an acute ischemic stroke to examine the efficacy and molecular mechanisms of action underlying these CHR. Results: CHR treatment significantly enhanced the survival rate of stroke mice, with BHD being the most effective CHR. All CHR were superior to recombinant tissue-type plasminogen activator (rt-PA) treatment in successfully ameliorating brain function, infarction, and neurological deficits in stroke mice that also paralleled to improvements in blood–brain barrier damage, inflammation, apoptosis, and neurogenesis. Transcriptome analyses reveals that a total of 774 ischemia-induced probe sets were significantly modulated by four CHR, including 52 commonly upregulated genes and 54 commonly downregulated ones. Among them, activation of neurogenesis-associated signaling pathways and down-regulating inflammation and apoptosis pathways are key common mechanisms in ischemic stroke protection by all CHR. Besides, levels of plasma CX3CL1 and S100a9 in patients could be used as biomarkers for therapeutic evaluation before functional recovery could be observed. Conclusion: Our results suggest that using CHR, a combinatory cocktail therapy, is a better way than rt-PA for treating cerebral ischemic-associated diseases through modulating a common as well as a specific group of genes/pathways that may partially explain the syndrome differentiation and treatment principle in TCM. Graphicalabstract: